Test Rozwoju Językowego (TRJ) as a psychometric tool for diagnosing developmental language disorders in Polish speaking children - Magdalena Smoczyńska (Maria Curie-Skłodowska University, Lublin, Poland, 2020)
The paper discusses Test Rozwoju Językowego or TRJ, a comprehensive language test for Polish speaking children aged 4;0-8;11, which was designed and standardized by a multidisciplinary team at the Educational Research Institute (Smoczyńska et. al, 2015). The test is composed of six subtests covering three areas of language: Vocabulary, Grammar and Discourse, as well as two dimensions: Comprehension and Production. The description of TRJ is preceded by a brief characteristic of the Developmental Language Disorders (DLD), previously referred to as Specific Language Impairment (SLI), and a review of diagnostic tools available for the diagnosis of language development in Polish speaking children.